Observer-based Fault Diagnosis for Time-Delay LPV Descriptor Systems. Issue 24 (2018) - Hamdi, H.; Rodrigues, M.; Mechmeche, C.; Benhadj Braiek, N.
Abstract: This paper deals with the problem of Fault Diagnosis (FD) for Descriptor-Linear Parameter Varying (D-LPV) systems with time delay. This proposed FD algorithm is based on an Adaptive Polytopic Observer. The proposed observer is able to detect and estimate faults despite the presence of disturbance. The existence conditions for the proposed observer are formulated by Linear Matrix Inequalities (LMI) which can be solved efficiently The effectiveness of the proposed approach is illustrated by a numerical example.